Digital health applications and health literacy: an explorative analysis - Aylin Imeri; Sabrina Schorr; Sebastian Merkel (Information Research: An International Electronic Journal)
Introduction. In 2020, Digital Health Applications (known as DiGA) have been introduced to the German healthcare system. DiGA are medical devices based on digital technologies that can be prescribed by physician and psychotherapists and reimbursed by health insurance companies. DiGA must demonstrate a positive healthcare effect, e.g. by improving of health literacy. Health literacy as a concept has received increasing attention in recent years but has also been subject to a vivid debate on its theoretical underpinning and methodological challenges.